By sword and plow France and the conquest of Algeria - Sessions, Jennifer E. (Cornell University Press, 2011)
In Sessions's view, French expansion in North Africa was rooted in contests over sovereignty and male citizenship in the wake of the Atlantic revolutions of the eighteenth century. Generously illustrated with examples of this imperialist iconography, Sessions's work connects a wide-ranging culture of empire to specific policies of colonization during a pivotal period in the genesis of modern France.